Topical dexpanthenol application improves healing of acute tympanic membrane perforations: an experimental study - Demirdelen, Sinem; İmamoğlu, Mehmet and Arslan, Selçuk and Sayğın, İsmail (ENT Updates, 2016)
Objective: To investigate the healing effects of topical dexpanthenol on acute tympanic membrane (TM) perforations in rats through observations of healing time and histopathological changes. Methods: A total of 20 Sprague-Dawley rats were included in the study. Every perforation was formed at the pars tensa of TMs with a size 2 mm in diameter. The right TM of each rat was treated with topical dexpanthenol for 2 days (treatment group); on the other hand, no topical agent was applied on the left TMs of rats (sham group). All TMs were examined under otomicroscopy at the third, fifth, and seventh days to determine the healing of TM perforations. Moreover, TMs were histopathologically examined to assess neovascularization, collagenization, fibroblastic activity, inflammatory cell positivity at the lamina propria (LP) layer of TMs. Results: The TM perforations in the treatment group healed significantly earlier (p<0.05). The collagenization at LP was significantly higher in the treatment group (p<0.05), while neovascularization and inflammatory cell positivity were significantly higher in the sham group (p<0.05). The fibroblastic activity was higher in the treatment group although no statistically significant difference was determined. Conclusion: The findings of the current study suggest that dexpanthenol may accelerate the healing of acute TM perforation.